Body concentration of caesium-137 in patients from Western Isles of Scotland. Issue 6792 (29th June 1991) - Isles, C G; Robertson, I; Macleod, J A; Preston, T; East, B W; Hole, D J; Lever, A F
Abstract : OBJECTIVES--To compare caesium-137 concentrations in patients from the Western Isles Health Board, Glasgow area, and other parts of the Scottish mainland, and to investigate the source of 137Cs in patients from the Western Isles. DESIGN--Study of hypertensive patients having electrolyte concentrations measured, including 137Cs. Interview by questionnaire of island subjects about intake of foods likely to contain radiocaesium and the source of these foods. Measurement of 137Cs and 134Cs in food, urine, and vegetation. SETTING--Scottish mainland and Western Isles, 1979-86. All measurements before Chernobyl nuclear accident. PATIENTS--413 consecutive patients referred to the blood pressure unit for investigation of hypertension. 60 from the Western Isles, including 44 from North Uist; 32 from North Uist participated in the dietary analysis. MAIN OUTCOME MEASURES--Concentration of radiocaesium in the body, urine, food, and vegetation. Islanders' consumption of local produce. RESULTS--Patients from the Western Isles had five times higher body concentrations of 137Cs (median 2.54 (interquartile range 1.25-3.73)) Bq/gK) than did patients from around Glasgow (0.47 (0.26-0.66) Bq/gK) and other parts of the Scottish mainland (0.42 (0.24-0.71) Bq/gK). Islanders often consumed local milk and mutton, but ate local fish rarely. 137Cs and 134Cs were present in coastal (21.6 Bq/kg 137Cs, 0.25 Bq/kg 134Cs) and moorland (135.9, 0.65 Bq/kg) grasses and in islanders' urine (2.01, 0.013 Bq/l). Lower concentrations (0.336, 0.004 Bq/l), were found in the urine of Glasgow controls (p less than 0.001 for both isotopes). CONCLUSIONS--Islanders have excess body 137Cs concentrations, most of which probably comes from local milk and lamb. The radioactivity is not above the recommended safety limit. The presence of 134Cs suggests that nuclear reprocessing is the source of some of the radiocaesium.